Associations of an Abnormal Physiological Score With Outcomes in Acute Intracerebral Hemorrhage: INTERACT2 Study. Issue 2 (February 2021) - Song, Lili; Wang, Xia; Ouyang, Menglu; Sun, Lingli; Chen, Xiaoying; Arima, Hisatomi; Sandset, Else C.; Delcourt, Candice; Wang, Jiguang; Chen, Guofang; Robinson, Thompson; Lindley, Richard I.; et al.
Abstract : Background and Purpose: We determined associations of physiological abnormalities (systolic blood pressure, glucose, and body temperature) and warfarin use with outcomes in spontaneous intracerebral hemorrhage. Methods: Post hoc analyses of INTERACT2 (Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial) comparing systolic blood pressure control (<140 versus <180 mm Hg) in 2839 hypertensive patients with intracerebral hemorrhage (onset <6 hours). Multivariable logistic regression defined associations of baseline scores assigned as 0 to 6 per 10 mm Hg systolic blood pressure increase (range, 150–220 mm Hg) and 0 or 1 for serum glucose (⩽6.5 versus >6.5 mmol/L), body temperature (⩽37.5 °C versus >37.5 °C), and warfarin use (no versus yes) and death or major disability (modified Rankin Scale scores 3–6 at 90 days). Results: Baseline score distribution was 0 (7.7%), 1 (15.6%), 2 (19.0%), 3 (19.1%), 4 (15.2%), 5 (11.6%), 6 (8.9%), and 7 (2.9%). After adjustment for baseline neurological severity and potential confounders, significant linear associations were evident for increasing (per point) score and death or major disability (odds ratio, 1.12 [95% CI, 1.07–1.17]), death (odds ratio, 1.15 [95% CI, 1.07–1.23]), and major disability (odds ratio, 1.10 [95% CI, 1.05–1.15]). Conclusions: Combination of abnormal physiological parameters and warfarin use is associated with poor outcomes in intracerebral hemorrhage. Effects of their early control is under investigation in INTERACT3 (Intensive Care Bundle With Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial). Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00716079. Abstract : Supplemental Digital Content is available in the text.